Rancang Bangun Evolved Network Management System Application (EVOMAC) pada Ekosistem Infrastruktur Jaringan Universitas Udayana - Pratama, Adhitya Bayu Rachman; Sukadarmika, Gede; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro; Vol 21 No 1 (2022): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2022)
Network Management System is a device with piles of capabilities to help the network engineer to utilize independent network component especially in a wide framework. Network Management System have the capabilities to identify, configure, monitor, update, and troubleshoots the wired also wireless network devices as well. Udayana University have been utilized some type of platforms to monitor and manage its network, those platforms are Cacti and OpenNMS. However, both of those platforms didn’t meet as what the experts called it as Integrated Network Management System. Thus, EVOMAC present as a solution to simplify the workflow of the network engineers. EVOMAC is an acronym for Evolved Network Management System Application that fused with OpenNMS, PostgreSQL, Telegram, and NodeJS. EVOMAC is also cooperates with four basic API methods that build its system such as POSTMethod, PUTMethod, GETMethod, and DELETEMethod. All of those API methods are the foundation of the command functions /start, /nodes, /addnode, /deletenode, /alarm, /category, and /requisition. Each of the command function has their own response time duration since it is related to the speed of the connected internet and the amount of people who has access to it.